Changes in the structural and gel properties of pork myofibrillar protein induced by catechin modification. (May 2017) - Jia, Na; Wang, Letian; Shao, Junhua; Liu, Dengyong; Kong, Baohua
Abstract: Different concentrations of catechin (0, 10, 50, 100 and 200 μmol/g protein) were added to pork myofibrillar protein (MP) suspensions, and the related changes in protein conformational and gel properties were investigated. The results showed that catechin at 200 μmol/g protein led to the greatest increase in the surface hydrophobicity of MP. A significant loss of thiols (SH) content was observed in MP in the presence of catechin. The low concentration of catechin of 10 μmol/g led to slight changes in the MP gel strength and water-holding capacity. However, catechin at higher concentrations (50, 100 and 200 μmol/g protein) caused severe deterioration of MP gelation. The microstructure and dynamic rheological properties confirmed the unfavorable effect of catechin on the MP gel properties. The results indicate that catechin caused changes in MP conformational and gel properties, which may be due to the catechin–MP covalent interactions and the exposure of hydrophobic domains caused by catechin. Highlights: Catechin addition changed the structure and gel properties of MP. Catechin increased the surface hydrophobicity and decreased the SH content of MP. Decrease of gel strength and WHC by catechin was concentration-dependency. SEM and rheological properties confirmed the unfavorable effect of catechin on gel.